Antibiotic-loaded polypropylene surgical meshes with suitable biological behaviour by plasma functionalization and polymerization. (December 2015) - Labay, C.; Canal, J.M.; Modic, M.; Cvelbar, U.; Quiles, M.; Armengol, M.; Arbos, M.A.; Gil, F.J.; Canal, C.
Abstract: Hernia repair is one of the most common operations in general surgery, and its associated complications typically relate to infections, among others. The loading of antibiotics to surgical meshes to deliver them locally in the abdominal hernia repair site can be one way to manage infections associated with surgical implants. However, the amount of drug loaded is restricted by the low wettability of polypropylene (PP). In this work, plasma has been used to tailor the surface properties of PP meshes to obtain high loading of ampicillin while conserving the desired biological properties of the unmodified samples and conferring them with antibacterial activity. It was demonstrated that the new surface chemistry and improved wettability led to 3-fold higher antibiotic loading. Subsequently, a PEG-like dry coating was deposited from tetraglyme with low-pressure plasma which allowed maintaining the high drug loading and kept cell properties such as chemotaxis, adhesion and morphology to the same levels as the untreated ones which have shown long-standing clinical success.